Porcelain gall bladder: a case report - Murugesan, Sowmya; R., Chandru; Ramakrishnan, Ramya; Raj, Rajiv; G., Kishore Kumar (International Surgery Journal, 2018)
Porcelain gall bladder is a rare entity and a morphological variant of chronic cholecystitis. Dystrophic calcification along with inflammatory scarring of the wall gives the porcelain nature to the gall bladder. Patients are mostly asymptomatic and incidentally diagnosed on X-ray, ultrasound or CT abdomen. In the early stages they can be a surprise as only a histopathological diagnosis. Prophylactic cholecystectomy is recommended in view of high risk of malignancy.